Cost analysis of two modalities of continuous renal replacement therapy. Issue 2 (25th October 2020) - Duriseti, Parikshit; Idrees, Najia; Aldairem, Atheer; Jaber, Bertrand L.; Balakrishnan, Vaidyanathapuram S.
Abstract: Background: Continuous veno‐venous hemofiltration (CVVH) and continuous veno‐venous hemodialysis (CVVHD) are costly therapies reserved for use in critically ill patients with kidney failure. Design: Quality improvement study at St. Elizabeth's Medical Center, Boston, MA, USA. Setting and participants: Members of nephrology and pharmacy department, working alongside intensive care unit nursing staff and hospital administration, undertook an initiative to transition from CVVH to CVVHD, to simplify therapy administration, lessen need for electrolyte repletion, and reduce total treatment‐related costs. Quality improvement plan: We postulated that conversion from CVVH to CVVHD would result in fewer filter clotting events, longer filter use (up to 72 hours), lower resource utilization, and confer overall cost benefit. Over 12 months, patients initiated on CVVH were identified. Following conversion to CVVHD, patients initiated on CVVHD over 9 months were identified. Patient characteristics, comorbidities, and hospital‐related outcomes, as well as CRRT‐related information including treatment modality, treatment duration, and treatment‐related costs were obtained. Measures: Daily treatment‐related costs, intensive care unit and hospital length of stay (LOS), and in‐hospital mortality. Results: During the baseline period, 77 patients were initiated on CVVH, and during the intervention period, 60 patients were initiated on CVVHD. Following conversion from CVVH to CVVHD, mean (±SD) daily total treatment cost decreased from $1813 ± $2143 to $775 ± $766 (P < 0.001). Conversion from CVVH to CVVHD had no impact on intensive care unit LOS (11.8 ± 9.7 vs. 12.4 ± 9.5 days; P = 0.53), hospital LOS (15.0 ± 11.1 vs. 16.4 ± 14.0 days; P = 0.89), or in‐hospital mortality (58% vs. 60%; P = 0.85). Limitations: Nursing costs, costs of dialysis machine utilization, phosphate repletion, and systemic anti‐coagulation were not studied. Conclusion: Transition from CVVH to CVVHD resulted in a significant cost benefit and reduced resource utilization. There was no difference in LOS and in‐hospital mortality between the two treatment modalities.